The Role of Authenticity in the Luxury Hotel Experience: A Mixed-Methods Study of the Hotel Sector in the United Kingdom - UMUT OGUZ (2020)
The experience economy has received substantial attention by many scholars across different disciplines and subject areas. Tourism has been one of the subject areas in which the notion of the experience economy has attracted substantial interest by scholars seeking to understand the concept and its outcomes. Nevertheless, studies have focused mainly on how memorable tourism experience has led to experience satisfaction and influences tourists’ future behaviours. Few studies have investigated the importance of memorable tourism experience and its impact on tourists’ perceived value, which could be considered to be of great importance in understanding tourist behaviour. Moreover, previous studies have tended to disregard factors such as perceived authenticity and its impact on the memorable tourism experience. This thesis aimed to investigate the relationship between perceived authenticity, perceived overall luxury value, memorable tourism experience and its impacts on satisfaction, attitude, memory and behavioural intentions. To do this, a sequential mixed-methods study was carried out with qualitatively interviewing 11 hotel managers across the United Kingdom in the first phase of the study and conducting a survey of 390 British hotel guests who had stayed in a hotel within the past year in the second phase. Analysing the in-depth interviews with hotel managers revealed that the perceived authenticity of the hospitality experience has influenced perceptions of luxury and memorability of the hotel experience. However, perceived authenticity might have both positive and negative impact on the luxury hospitality business, due to restrictions on historic buildings. Moreover, these findings were later tested by using Partial Least Square (PLS) structural equation modelling with the data from the British hotel guests. The findings confirmed that perceived authenticity has a direct impact on the memorable hospitality experience construct. The results showed that a more memorable tourism experience would lead to a higher level of perceived luxury value and satisfaction. This showed that higher satisfaction and memorability would lead to more positive behavioural intentions for hotel guests in the future. This thesis has had implications both for theory and practice. First, it revealed the importance of designing an authentic experience in the hospitality business, since it influenced guests’ perceptions of the memorability of the hospitality experience. Future studies could include measures of perceived authenticity and memorable hospitality experience to examine service experience in different contexts. Second, a memorable hospitality experience was found to be a significant indicator of perceived luxury value, which leads to a higher level of satisfaction. This finding might help service providers in the hospitality industry to design better luxury hotel experiences.